2000
DOI: 10.1080/003655900750016841
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Prostaglandins in Pathogenesis of Nocturnal Enuresis in Children

Abstract: The results of the study suggest that changes in renal function are due not to a higher secretion of prostaglandins in nocturnal enuresis but to the relative dominance of their effect as compared with other physiologically active substances that simultaneously act on renal tubular cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…The initial findings of decreased vasopressin (AVP) levels 11 associated with increased urine production with low osmolality overnight were recently 12 confirmed 7,8 . Due to the reduction of nocturnal polyuria and enuresis by the vasopressin 13 analogue desmopressin (1-desamino-8-D-arginine vasopressin) (dDAVP), the decreased 14 nocturnal vasopressin secretion hypothesis became widely accepted 1 . 15 Although evidence based results show superiority of dDAVP above placebo, only 30 % of 16 patients reach complete continence, suggesting that probably not all patients with MNE have 17 polyuria or are dDAVP-responsive 7,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The initial findings of decreased vasopressin (AVP) levels 11 associated with increased urine production with low osmolality overnight were recently 12 confirmed 7,8 . Due to the reduction of nocturnal polyuria and enuresis by the vasopressin 13 analogue desmopressin (1-desamino-8-D-arginine vasopressin) (dDAVP), the decreased 14 nocturnal vasopressin secretion hypothesis became widely accepted 1 . 15 Although evidence based results show superiority of dDAVP above placebo, only 30 % of 16 patients reach complete continence, suggesting that probably not all patients with MNE have 17 polyuria or are dDAVP-responsive 7,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The problem was solved not only for the case of nocturnal enuresis in children but also as the more general problem of the physiological regulation of renal functions in humans. An increase in the renal excretion of autacoids was found [14]. This increase correlated with an increase both in the excretion of osmotically active substances, in particular, sodium ions, and in the reabsorption of solute-free water.…”
Section: Resultsmentioning
confidence: 90%
“…This increase correlated with an increase both in the excretion of osmotically active substances, in particular, sodium ions, and in the reabsorption of solute-free water. In this case, prostaglandin Ö 2 was one of the autacoids [14]. Prostaglandin E 2 is known to inhibit the effect of vasopressin, and its increased secretion can be expected to decrease the reabsorption of solute-free water.…”
Section: Resultsmentioning
confidence: 97%
“…Although these theories, which include behavioral, developmental, psychological, genetic, neurological, urodynamic, and organic causes, are diverse and may be able to explain selected cases, there is no single explanation for nocturnal enuresis [2,3]. Clearly, the vast majority of children with nocturnal enuresis do not suffer from psychiatric, neurological, or urologic disturbances, and investigation along these lines was worthless.…”
Section: Discussionmentioning
confidence: 98%
“…Recent research has helped to correct some traditional misconceptions and unveil the underlying pathophysiological mechanisms. It has been demonstrated that nocturnal enuresis is a heterogeneous disorder with various pathophysiological causes, resulting in a mismatch between the nocturnal bladder capacity and the amount or urine produced during sleep at night, in association with a simultaneous failure of conscious arousal in response to the sensation of bladder fullness [2]. Nowadays, nocturnal enuresis is not considered a self-limited condition, but a disease that necessitates appropriate diagnostic and therapeutic work-up.…”
Section: Introductionmentioning
confidence: 99%